Vice, crime and poverty: how the Western imagination invented the underworld - Kalifa, Dominique (European perspectives, 2019)
In the den of horror -- Courts of miracles -- "Dangerous classes" -- Empire of lists -- The disguised prince -- The grand dukes' tour -- Poetic flight -- Ebbing of an imaginary -- Slow eclipse of the underworld -- Persistent shadows -- Roots of fascination.